BRAF mutation detection in indeterminate thyroid cytology specimens1: Underlying cytologic, molecular, and pathologic characteristics of papillary thyroid carcinoma. Issue 4 (7th August 2012) - Ohori, N. Paul; Singhal, Rashi; Nikiforova, Marina N.; Yip, Linwah; Schoedel, Karen E.; Coyne, Christopher; McCoy, Kelly L.; LeBeau, Shane O.; Hodak, Steven P.; Carty, Sally E.; Nikiforov, Yuri E.
Abstract: BACKGROUND: BRAF mutations are highly specific for papillary thyroid carcinoma (PTC) and many cytology specimens with BRAF mutations are expected to demonstrate cytologic features typical of PTC. However, indeterminate thyroid cytology cases are inevitable and understanding the significance of the BRAF mutation within the context of the Bethesda System for Reporting Thyroid Cytopathology would be valuable. METHODS: Thyroid cytology cases submitted for conventional cytomorphologic evaluation and BRAF mutational analyses were selected from the authors' cytopathology files from April 2007 to October 2011. From this group, the diagnostic usefulness of BRAF mutations in indeterminate and malignant cases was assessed and analyses of cytologic and histopathologic features associated with the mutations in this gene were performed. RESULTS: A total of 131 cases with a BRAF mutation were identified. Of these, 119 underwent surgical pathology resection follow‐up and demonstrated PTC. Approximately 75% of the cases were cytologically diagnosed as being positive for malignancy and these cases were associated with both the classic and tall cell variants of PTC at the time of resection, a greater likelihood of extrathyroidal extension, and the V600E type of BRAF mutation. In contrast, BRAF ‐mutated cases with diagnoses of atypia of undetermined significance/follicular lesion of undetermined significance (AUS/FLUS) and follicular neoplasm/suspicious for follicular neoplasm were found to be more strongly associated with the follicular variant of PTC, a K601E BRAF mutation, and a lower likelihood of extrathyroidal extension. However, a subset of AUS/FLUS cases with the V600E BRAF mutation appeared to represent sampling variability of the classic or tall cell variants of PTC. CONCLUSIONS: Bethesda thyroid diagnoses in the setting of a BRAF mutation reflect differences in PTC subtypes, the nature of cytology specimens, and molecular characteristics. Cancer (Cancer Cytopathol) 2013;121:197–205. © 2012 American Cancer Society. Abstract : The BRAF mutation is found not only in malignant cytology cases but also in indeterminate thyroid cases. For these indeterminate cases with a BRAF mutation, the authors find that the specific cytology diagnoses (atypia of undetermined significance/follicular lesion of undetermined significance, follicular neoplasm/suspicious for follicular neoplasm, and suspicious for malignancy) reflect differences in the nature of cytology specimens, molecular characteristics, and histologic subtypes of papillary thyroid carcinoma.